2017
DOI: 10.1002/biof.1362
|View full text |Cite
|
Sign up to set email alerts
|

The molybdenum cofactor enzyme mARC: Moonlighting or promiscuous enzyme?

Abstract: Molybdenum (Mo) is present in the active center of eukaryotic enzymes as a tricyclic pyranopterin chelate compound forming the Mo Cofactor (Moco). Four Moco containing enzymes are known in eukaryotes, nitrate reductase (NR), sulfite oxidase (SO), xanthine oxidoreductase (XOR), and aldehyde oxidase (AO). A fifth Moco enzyme has been recently identified. Because of the ability of this enzyme to convert by reduction several amidoximes prodrugs into their active amino forms, it was named mARC (mitochondrial Amidox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 84 publications
0
34
0
Order By: Relevance
“…Several enzymes are thought to moonlight often by impacting transcription. These include the molybdenum co-factor enzyme mARC [83], holocarboxylase synthase [84], pyruvate kinase, lactate dehydrogenase, and succinate dehydrogenase [85]. PCCB mRNA accounts for 0.02% total hepatic mRNA [86] and this may reflect moonlighting roles.…”
Section: Reviewmentioning
confidence: 99%
“…Several enzymes are thought to moonlight often by impacting transcription. These include the molybdenum co-factor enzyme mARC [83], holocarboxylase synthase [84], pyruvate kinase, lactate dehydrogenase, and succinate dehydrogenase [85]. PCCB mRNA accounts for 0.02% total hepatic mRNA [86] and this may reflect moonlighting roles.…”
Section: Reviewmentioning
confidence: 99%
“…The enzyme from humans has been proposed to reduce a broad range of N-hydroxylated compounds receiving electrons from cytochrome b5 (Gruenewald et al, 2008 ) and to reduce nitrite to nitric oxide (Sparacino-Watkins et al, 2014 ). A number of controversies over the function, subcellular localization and whether the newly discovered enzyme binds to sulfurated or oxo Moco, have been reviewed (Llamas et al, 2017 ).…”
Section: Fe-s and Moco Enzymesmentioning
confidence: 99%
“…Furthermore, recent studies suggest that mARC is important for organisms to ensure reductive detoxification strategies, for example of toxic hydroxylamines (4) or mutagenic N-hydroxylated nucleobases (5,12). After its discovery, subsequent studies have shown that the enzyme is able to reduce the full range of Noxygenated compounds, including the capacity to reduce inorganic nitrite to nitric oxide (13) and N ω -hydroxy-L-arginine to arginine (14). All annotated genomes of mammals appear to possess two copies of mARC genes, with both copies showing strong similarities on nucleotide and amino acid levels, thus making a discrimination difficult, but defining them as paralogous proteins.…”
mentioning
confidence: 99%